1972
DOI: 10.2337/diab.21.12.1168
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-acetyl-beta-glucosaminidase Activity in Diabetic Patients

Abstract: In a group of seventy-three diabetics, a statistically significant (P < 0.001) increase (+ 41 per cent) of serum N-acetyl-beta-glucosaminidase activity was found. The enzyme level seemed to correlate with both the vascular complications (either microangiopathic or macroangiopathic in nature) and the blood sugar level measured simultaneously. In fact, in patients with moderately elevated glycemia (145 mg./100 ml. ± 41) and without vasculopathies, the enzymatic activity was slightly changed (P > 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
16
1

Year Published

1977
1977
1989
1989

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 0 publications
5
16
1
Order By: Relevance
“…The present results are in accordance with those of earlier studies, which have shown an elevation of serum GLU [4,8,25] and NAG [2,6,11,25] in patients with diabetes mellitus. Further, in the present study the levels of the two lysosomal enzymes in the diabetics were significantly higher in subjects with non-proliferative retinopathy (p < 0.05 for both enzymes).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The present results are in accordance with those of earlier studies, which have shown an elevation of serum GLU [4,8,25] and NAG [2,6,11,25] in patients with diabetes mellitus. Further, in the present study the levels of the two lysosomal enzymes in the diabetics were significantly higher in subjects with non-proliferative retinopathy (p < 0.05 for both enzymes).…”
Section: Discussionsupporting
confidence: 94%
“…Very high enzyme levels have been encountered in diabetics with a severely deranged metabolic balance [2,4,10]. Although a similar correlation was also detected in the present study, all of the patients were clinically in fairly good glycaemic control and the blood glucose level was similar in the groups with and without non-proliferative retinopathy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations